Study on Different Fractions of Organic Molecules in the Baltic Sea Surface Microlayer by Spectrophoto- and Spectrofluorimetric Methods - Drozdowska, Violetta; Kowalczuk, Piotr; Konik, Marta; Dzierzbicka-Glowacka, Lidia (Frontiers in Marine Science, 2018)
The sea surface microlayer (SML), created by surface active organic molecules (called: surfactants), is a highly active interface between the sea and the atmosphere. In this study we used the dissolved organic matter absorption and fluorescence properties for description of changes in molecular size and weight distribution of organic molecules as well as in their composition in the SML compared to subsurface water layer (SS), of 1 m depth. Data were collected during three research cruises in the Baltic Sea. Spectral values of the CDOM absorption coefficient were higher in the SML about 29 % (in the UV light) to 17 % (in a blue spectral range), while spectral slope coefficients at different spectral ranges, S_Δλ, were lower in SML by 2.3 and 10.5% compared to SS in 275-295 nm and 350-400 nm, respectively. The fluorescence intensities of main Excitation Emission Matrix spectra peaks belonging to the main fluorescing components of marine organic matter, called: A, C, M, T, were higher in SML by 41, 43, 41 and 14% compared to SS. The ratio of fluorescence intensities, ((M+T))⁄((A+C) ) and humification index, HIX, values in SML were, respectively higher by 17.9% and lower by 10.7 % compared to SS. These two parameters where coupled with inverse non-linear relationship. This relationship indicated faster removal of humic components of high MW in the SML compared to SS. We have observed decreasing trend of spectral slope ratio, S_R, with increasing salinity. The S_R decreased 33.5 and 23.6 % in the SML and SS, respectively in the salinity gradient from 4.5 to 7.94 (of practical salinity ). The fluorescence intensity of all FDOM peaks decreased by in the same salinity gradient. The decrease rate was higher in SML for all fluorescing peaks by 34, 36 and 26 % for A, C and M, respectively than in the SS. Decrease rate indicated the susceptibility to photochemical degradation of respective peaks. This effect was strongest for C while T peak was almost unbleached. The fluorescence intensity decrease rate was smaller in SS what indicated shielding effect of the SML.